Pengaruh Persaingan Politik terhadap Anggaran Kesehatan: Studi Kasus pada Kabupaten dan Kota di Indonesia - Runtiningsih, Sri; Susamto, Akhmad Akbar (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This study aims to analyze the effect of political competition on health budgets in Indonesia. The analysis was conducted using a fixed-effects panel data regression approach for Indonesia’s regencies and municipalities between 2009 and 2019. To obtain robust results, this study uses three different measures of political competition, namely the Multiparty Margin Index, the Herfindahl-Hirschman Index (HHI), and the Effective Number of Parties (ENP) Index. The estimation results show that only legislative political competition has a significant and consistent negative effect on the health budget, it is similar to the Leviathan Model theory.